Psychotria nilgherensis (Rubiaceae), a new combination replacing P. elongata - Govaerts, Rafaël; Chakrabarty, Tapas (Phytotaxa, 2017)
The genus Grumilea was established by Gaertner (1788: 138, t. 28, f. 2) on the basis of a single species, G. nigra Gaertner from Sri Lanka. The genus was subsequently recognized and treated by a number of authors such as Candolle (1830: 495), Wight & Arnott (1834: 432), Miquel (1857: 295) and Thwaites (1859: 147). However, Bentham & Hooker (1873: 123) combined Grumilea with Psychotria Linnaeus (1759: 929, 1364), nom. cons., a delimitation that was accepted by later workers (e.g., Mabberley 2008: 377). Hooker (1880: 161) treated Grumilea as a Section of Psychotria. Wight (1845: 16, t. 1036) described a species, Grumilea elongata from Tamil Nadu, India which was transferred to Psychotria by Hooker as Psychotria elongata (Wight) Hooker (1880: 163). This name was used in most of the subsequent floristic treatments (e.g., Trimen 1894; Brandis 1906; Gamble 1921; Fyson 1932; Sebastine & Vivekananthan 1967; Matthew & Rani 1983; Swaminathan 1987; Mohanan & Henry 1994). Sohmer (1977: 381), realizing that the name P. elongata is a later homonym of two names published by Bentham (1853: 32) and Beddome (1872: t. 17), applied a new name, P. fosbergii Sohmer which was accepted and used by Deb & Gangopadhyay (1989: 70, f. 29) in their revision of the genus Psychotria. Unfortunately, they overlooked the fact that this name is also a later homonym of P. fosbergii Steyermark (1972: 630). Later, Kiehn published the replacement name P. sohmeri Kiehn (1986: 215) and this was used as the correct name by Sohmer (1987: 339). Two years later, Suresh proposed another replacement name, P. glandulosa Suresh (1988: 229). As this is a later replacement name, it is superfluous and illegitimate. Unfortunately, all these authors overlooked the fact that Kuntze (1891: 957) published the name Uragoga nilgherensis replacing Grumilea elongata which, if transferred to Psychotria, becomes the earliest valid replacement name for the Wight’s species. Hence the necessary new combination is proposed below.